2020
DOI: 10.1038/s41598-020-70215-7
|View full text |Cite
|
Sign up to set email alerts
|

A model of the PI cycle reveals the regulating roles of lipid-binding proteins and pitfalls of using mosaic biological data

Abstract: the phosphatidylinositol (pi) cycle is central to eukaryotic cell signaling. its complexity, due to the number of reactions and lipid and inositol phosphate intermediates involved makes it difficult to analyze experimentally. computational modelling approaches are seen as a way forward to elucidate complex biological regulatory mechanisms when this cannot be achieved solely through experimental approaches. Whilst mathematical modelling is well established in informing biological systems, many models are often … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Another class of phospholipids that emerged as important were the phosphatidylinositols (PI). These lipids are the central actors in the PI and PIP 2 cycles underpinning several mammalian cell signaling pathways ( 32 ). There, PI is converted into phosphatidylinositol-4-phosphate (PI4P), which is further converted into phosphatidylinositol-4,5-bisphosphate (PIP 2 ) via various phosphokinases.…”
Section: Discussionmentioning
confidence: 99%
“…Another class of phospholipids that emerged as important were the phosphatidylinositols (PI). These lipids are the central actors in the PI and PIP 2 cycles underpinning several mammalian cell signaling pathways ( 32 ). There, PI is converted into phosphatidylinositol-4-phosphate (PI4P), which is further converted into phosphatidylinositol-4,5-bisphosphate (PIP 2 ) via various phosphokinases.…”
Section: Discussionmentioning
confidence: 99%
“…Another class of phospholipids that emerged as important were the phosphatidylinositols (PI). These lipids are the central actors in the PI and PIP 2 cycles, underpinning several mammalian cell signaling pathways . There, PI is converted into phosphatidylinositol-4-phosphate (PI4P), which is further converted into phosphatidylinositol-4,5-bisphosphate (PIP 2 ) via various phosphokinases.…”
Section: Discussionmentioning
confidence: 99%
“…These lipids are the central actors in the PI and PIP 2 cycles, underpinning several mammalian cell signaling pathways. 35 There, PI is converted into phosphatidylinositol-4-phosphate (PI4P), which is further converted into phosphatidylinositol-4,5-bisphosphate (PIP 2 ) via various phosphokinases. PIP2, on the other hand, is a component of the phosphatidylinositol 3-kinase (PI3K) pathway that has been extensively implicated in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…159 Mazet et al have described an ODE-based model on the phosphatidylinositol cycle and suggested that lipid-and protein-binding proteins help regulate PtdIns(4,5)P2 and InsP3 in GPCR signalling. 165 These studies have shown the potential of mathematical models in elucidating platelet signalling through the interplay of protein phosphorylation and phosphoinositide metabolism and predicting platelet homeostasis and activation. However, these models did not account for other phosphoinositide isomers.…”
Section: Systems Biology and Mathematical Modellingmentioning
confidence: 99%